2017
DOI: 10.1038/s41598-017-15479-2
|View full text |Cite
|
Sign up to set email alerts
|

Acinar injury and early cytokine response in human acute biliary pancreatitis

Abstract: Clinical acute pancreatitis (AP) is marked by an early phase of systemic inflammatory response syndrome (SIRS) with multiorgan dysfunction (MODS), and a late phase characterized by sepsis with MODS. However, the mechanisms of acinar injury in human AP and the associated systemic inflammation are not clearly understood. This study, for the first time, evaluated the early interactions of bile acid induced human pancreatic acinar injury and the resulting cytokine response. We exposed freshly procured resected hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Recent studies have revealed that the initiating events of SAP, including zymogen activation and cell death, occur in pancreatic acinar cells (PACs) [ 3 ]. Furthermore, the earliest immune response in acute pancreatitis was shown to originate within the PACs that activate circulating immune cells to induce a systemic inflammatory response [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that the initiating events of SAP, including zymogen activation and cell death, occur in pancreatic acinar cells (PACs) [ 3 ]. Furthermore, the earliest immune response in acute pancreatitis was shown to originate within the PACs that activate circulating immune cells to induce a systemic inflammatory response [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been shown in experimental models of AP using L-arginine that there could be PSC activation and early fibrosis even after the first episode of AP [11]. In our recent studies using human pancreatic acini, we could show that PSC activation could occur even after bile acid-mediated injury [4]. However, clinical acute biliary pancreatitis does not progress to CP.…”
mentioning
confidence: 75%
“…This is the sentinel acute pancreatitis event (SAPE) hypothesis that defines pancreatitis as a disease spectrum [1]. Even though several clinical and bench studies have provided insights into the pathophysiology of the disease [2][3][4][5], there is still no modality to accurately predict the progression of RAP to CP. This gap in understanding has likely, at least in part, precluded development of any specific interventions that could prevent progression of RAP to CP or reverse the changes of CP.…”
mentioning
confidence: 99%
“…Another study reported a similar effect of pro-inflammatory interferon-β and anti-inflammatory cytokine IL-10 in macrophages after LPS treatment in vitro 49 . Considering that pro-inflammatory cytokines are crucially associated with the pathogenesis of acute pancreatic injury 50 , 51 , the impaired homeostasis between pro- and anti-inflammatory mediators in acinar cells might predispose LPS-challenged autophagy-deficient Atg7 Δpan mice to developing more severe pancreatic injury than normal mice.…”
Section: Discussionmentioning
confidence: 99%